Use of Emojis as a Means of Communication among Caleb University Students - Okunade Joshua Kayode; Damilola Yusuf (Britain International for Academic Research (BIAR-Publisher), 2026)
This study was conducted to examine how the Nigerian youth uses emojis as a means of communication. Emojis are now the most efficient method to convey feelings and emotions in textual conversation. The purpose of this study was to determine how emojis affected people's vocabulary, ideas, and facial expressions both online and in daily life. How have traditional forms of language affected online platforms such is WhatsApp, Instagram, Facebook, and Snapchat. There were more of the drums, firewood, and birds in the olden days, but we are now in the jet age where we can just sit down comfortably in our homes and offices to send a piece of information. This study also looks into how young people in Nigeria utilize emojis for communication. Emojis have significantly increased in popularity as visual symbols for emotions, moods, and thoughts in online exchanges in recent years. The theory that underpins the findings is the Uses and Gratification theory. The goal of this project is to examine how emojis function within the particular cultural setting of Nigeria and comprehend how they affect young people's communication dynamics. Emoji as has added more understanding to a message. The results of this study will improve our knowledge of how emojis influence cultural expression and communication among young people in Nigeria. The results of this study improved our knowledge of how emojis influence cultural expression and communication among young people in Nigeria. The study concludes that emojis have a substantial impact on communication by enriching message interpretation, facilitating emotional expression, and enabling users to convey information quickly, effectively, and succinctly. As digital communication continues to evolve, emojis are likely to remain important tools for enhancing meaning and fostering more expressive online interactions.